2020
DOI: 10.3389/fneur.2020.00997
|View full text |Cite
|
Sign up to set email alerts
|

From Acute to Chronic Tinnitus: Pilot Data on Predictors and Progression

Abstract: Little is known about the transition from acute tinnitus to chronic tinnitus. By means of this study, we are attempting to close this gap by presenting prospective pilot data of patients with acute tinnitus, followed by tracking their condition's trajectory over a period of 6 months. Forty-nine patients presenting with acute tinnitus (duration < 28 days) were recruited in two clinics. We recorded demographic and clinical tinnitus-related data as well as data on personality, health, treatments, and life-style, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…We here suggest that the confounding factor in the T-group is a gradual increase in hyperacusis characteristics. Before we discuss this aspect in more detail, it is important to note that two recent trials also investigated the transition of tinnitus from acute to chronic over a period of 6 months ( 29 , 30 ) and found that the average tinnitus distress moderately improved over time. Neither of these studies, however, analyzed tinnitus over longer durations or separated its features from the co-occurrence of hyperacusis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We here suggest that the confounding factor in the T-group is a gradual increase in hyperacusis characteristics. Before we discuss this aspect in more detail, it is important to note that two recent trials also investigated the transition of tinnitus from acute to chronic over a period of 6 months ( 29 , 30 ) and found that the average tinnitus distress moderately improved over time. Neither of these studies, however, analyzed tinnitus over longer durations or separated its features from the co-occurrence of hyperacusis.…”
Section: Discussionmentioning
confidence: 99%
“…A hitherto, largely unexplored, factor is the duration of chronic tinnitus. In three recent publications, the transition from acute to chronic tinnitus was examined (28)(29)(30). One study included normal hearing subjects with tinnitus lasting longer than 6 months (28) and classified patients into 3 categories according to the tinnitus duration: (i) acute, < 1 month (ii) chronic, > 6 months, (iii) subacute, between 1 and 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively little is known about the course of tinnitus over time [ 7 , 105 , 106 , 107 ]. There are a lot of factors contributing to this.…”
Section: Discussionmentioning
confidence: 99%
“…A recent longitudinal study found that 18.4% of acute tinnitus patients had complete remission of tinnitus within 6 months. There was no change in tinnitus characteristics in patients with their tinnitus persistent ( Vielsmeier et al, 2020 ). However, the exact mechanism of the chronization of tinnitus remains a mystery.…”
Section: Introductionmentioning
confidence: 95%